Women's economic empowerment in sub-Saharan Africa: Evidence from cross-national population data - Eunice Williams; Sabu S. Padmadas; Heini Vaisanen (Demographic Research, 2022)
Background: Women's economic empowerment (WEE) has attracted high-level policy interest, and is recognized as a central, cross-cutting outcome, and the cornerstone for achieving Sustainable Development Goals. However, it lacks a standardised definition and standard, measurable, and comparable indicators, and is plagued by large data gaps, particularly in sub-Saharan Africa (SSA). Objective: We examine the extent of WEE in SSA. Our goal is to identify WEE country typologies explaining the variation in and contributing domains of WEE in each country. Methods: Using recent DHS data in 33 countries, we apply principal component analysis to generate a WEE score based on 9 indicators in order to better understand the contributors underlying this score and derive country typologies. Results: Overall, WEE is low but it varies markedly by country. It is typically explained by educational attainment, employment, and land ownership among women alone or in combination with men. We identified 5 typologies of WEE: (1) instrumental agency explained by high educational attainment, (2) instrumental agency explained by land ownership, (3) individual economic advancement explained by high employment rates, (4) basic-level economic empowerment, and (5) low-level economic empowerment. Conclusions: The level of WEE in SSA varies by country. The factors affecting the level also vary and can be divided into 5 typologies characterising the type of WEE. Contribution: Our results provide timely evidence for the increasing push to achieve WEE and highlight potential priority areas for policy and programme interventions.